Von-Hipple Lindau syndrome with family history: a case report and seventeen years follow-up study - Fan, XueMei; Wang, Shuai; Chen, Tianwen; Hu, Wei; Yang, Hui (Frontiers in Oncology, 2024)
Background: Von-Hipple Lindau syndrome is an uncommon autosomal dominant disorder. 17 years ago we diagnosed a young woman with VHL syndrome validated by Sanger sequencing, her family members were genetically tested as well, and 187 healthy people were randomly selected for VHL genetic testing as controls. We analyze the clinical and genetic characteristics of VHL syndrome in a Chinese lineage and with 17-year follow-up. Case presentation: A woman was finally diagnosed with VHL syndrome due to the detection of a missense mutation c.353T > C in exon 2 of the short arm of chromosome 3, which resulted in a leucine substitution at amino acid 118 of the encoded protein by a proline, which may be thought the main cause of the disease. The same mutation was observed in two other family members, their clinical symptoms are not entirely identical. However, this mutation was not found in other family members or 187 healthy controls. She clinically presented with central nervous system hemangioblastomas, clear renal cell carcinoma, and pancreatic neuroendocrine neoplasms, despite the multi-organ involvement and several relapses during the disease, the patients survive well for sha was treated with aggressive surgery early in the course of the plaguing symptoms, whereas patients who are not aggressively treated have a poorer prognosis.The clinical presentation of VHL syndrome is atypical, and early identification and treatment of VHL syndrome is possible by genetic testing techniques. Multiple relapses occurred during the course of the disease, but early diagnosis and aggressive treatment allowed the patients to survive well.